Human adaptation in ancient Mesoamerica: empirical approaches to Mesoamerican archaeology - Gonlin, Nancy, editor; French, Kirk D., editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2016)
"From the hydrological engineering behind Teotihuacan's layout, to the complexities of agriculture and sustainability in the Maya lowlands, to the nuanced history of abandonment along different lineages and households in Maya centers, Human Adaptation in Ancient Mesoamerica covers a diverse array of topics which explore human adaptation in Mesoamerica to social, political, economic, and environmental factors.--Provided by publisher.
Section 1: Introduction -- Foreward / by George R. Milner -- Empirical archaeology and human adaptation in Mesoamerica / by Kirk D. French and Nancy Gonlin -- Section 2: Water & land -- Water temples and civil engineering at Teotihuacan, Mexico / by Susan Toby Evans and Deborah L. Nichols -- Measuring the impact of land cover change at Palenque, Mexico / by Kirk D. French and Christopher J. Duffy -- Complementarity and synergy: stones, bones, soil and toil in the Copan Valley, Honduras / by John D. Wingard -- Section 3: Population & settlement studies -- Chronology, construction, and the abandonment process: a case study from the classic Maya kingdom of Copan, Honduras / by AnnCorinne Freter and Elliot M. Abrams -- The map leads the way: archaeology in the Mixteca Alta, Oaxaca, Mexico / by Stephen L. Whittington and Nancy Gonlin -- Section 4: Reconstruction & burial analysis -- The excavation and reconstruction of Group 8N-11, Copan, Honduras: the process of discovery and re-discovery / by Randolph J. Widmer and Rebecca Storey -- The Maya in the middle: an analysis of sub-royal archaeology at Copan, Honduras / by David M. Reed and W. Scott Zeleznik -- Section 5: Political economy -- Life under the classic Maya Turtle Dynasty of Piedras Negras, Guatemala / by Zachary Nelson -- The production, exchange, and consumption of pottery vessels during the classic period at Tikal, Peten, Guatemala / by Kirk Damon Straight -- Section 6: Reflections & discussion -- Forty years in Peten, Guatemala: a hagiographic prosopography / by Don S. Rice and Prudence M. Rice -- Two Katun archaeologist / by David Webster.
Keywords: Mayas -- Social conditions; Mayas -- Antiquities; Human ecology -- Mexico -- History -- To 1500; Human ecology -- Central America -- History -- To 1500; Social archaeology -- Mexico; Social archaeology -- Central America; Environmental archaeology -- Mexico; Environmental archaeology -- Central America; Mexico -- Antiquities; Central America -- Antiquities